If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4u+4=-4(u+1)
We move all terms to the left:
4u+4-(-4(u+1))=0
We calculate terms in parentheses: -(-4(u+1)), so:We get rid of parentheses
-4(u+1)
We multiply parentheses
-4u-4
Back to the equation:
-(-4u-4)
4u+4u+4+4=0
We add all the numbers together, and all the variables
8u+8=0
We move all terms containing u to the left, all other terms to the right
8u=-8
u=-8/8
u=-1
| 14=8x-10` | | (2x+1)^3-6x=0 | | -3y+10=100 | | 5k+16=51 | | d+1.2=9.82 | | 6-8x=7x-9=18 | | -2(x-4)+5x=32 | | 5x+12=6x+11 | | w-2=42 | | x-22=-42 | | u+1=16 | | 4.5+0.2m=6.1 | | Y=-3x-1+7 | | 5x+3=2(15x-29) | | −1/2x−(1/2x+4)+12=17x−6(3x+5/6) | | 12=10+p/8 | | 12x-8=-2x+118 | | x=12x+10 | | (4x+(2x+6=180 | | -4=n/7-2 | | 20=p-5 | | 6x+4=-86 | | 72=-6(-6-3z) | | 13=d|6 | | -7x-10=-11x+14 | | x/1.6=3.1 | | 31=10-3b | | 2z+3=37 | | x+14=- | | 4=|11+3x| | | 2x^2-7x+3=x^2+2x+13 | | -3n+1=-53 |